Effect of X-Ray Radiation on Electro-Optical Characteristics of CR-39 Sheets by Using Microwave and FTIR Spectroscopy Techniques - Al-Jobouri, Hussain Ali; Sulaiman, Jameel M A; Jarallah, Ahamed S (Al-Nahrain Journal of Science, 2012)
The effect of x-ray radiation has been studied by measurement of the permittivity (p) and transmission ratio (T%) on CR-39 sheets a nuclear solid state track detector by microwave and Fourier Transformer Infrared)FTIR(spectroscopy techniques respectively. The permittivity (p) increases with dose increase of x-ray radiation from 2-6.032 mGy. In addition, obtained there was dropping in the permittivity (p) from the value 600 CV−1m−1 at the radiation dose 6.032 mGy to the value 47 CV−1m−1. And there was reciprocal point at 10.5 mGy, then still (εp) value constant at this value with increasing of radiation dose until to 18 mGy. The absolute difference (DT) of the transmission ratio (T%), which is measured by FTIR spectroscopy between irradiated-TR and unirradiated-T0 [DR  |TR  T0|] of CR-39 sheets, has been decreased at the wave number 2250 cm-1 and 2450 cm1 to a reciprocal point of 14. 0 mGy and then increased to 18.0 mGy. This study suggest the use of CR-39 sheets as dosimeter for x-ray radiation by measuring the permittivity (p) and the transmission ratio (T%).